Promoting inclusive engineering identities in first-year engineering courses: paper - Atadero, Rebecca A., author; Paguyo, Christina H., author; Rambo-Hernandez, Karen E., author; Henderson, Heather Lysbeth, author; ASEE, publisher (Colorado State University. Libraries, 2016)
In order to cultivate a diverse and inclusive engineering student population, engineering programs must purposefully teach engineering students to identify as engineers, appreciate diversity, and work in inclusive environments. In this NSF-funded project, we collaborate with engineering faculty to design and implement interventions for first-year engineering students to strengthen their engineering identities and raise their awareness of how diversity benefits the engineering profession. This paper and poster describe the activities implemented during the first intervention year of the project and preliminary findings. The paper addresses the following questions: 1. What experimental intervention activities potentially support engineering students in developing engineering identities and appreciating diversity? 2. What patterns emerge in participants' engineering identities and appreciation of diversity after the experimental intervention activities have been implemented? Do these patterns differ by section or by sex? To answer the first inquiry, we describe the experimental intervention activities and the classroom contexts in which they were implemented. Then a quantitative analysis of survey data is summarized to address the second inquiry. We conclude this paper with ideas about how to improve the efficacy and transportability of experimental intervention activities so they can be adapted for multiple classroom environments and professor teaching styles.
Paper given at the ASEE's 123rd Annual Conference & Exposition in New Orleans, Louisiana, USA, June 26-28, 2016.
Paper ID #14895.
Keywords: engineering education; diversity in engineering; first-year engineering students; engineering identity; women; underrepresented minorities; inclusive engineering; engineering curriculum